Peran Guru Pendidikan Agama Islam Dalam Menanggulangi Dampak Negatif Media Sosial di SMAN 8 Kecamatan Mandau Kabupaten Bengkalis – Riau - Nur Afif; Agus Nur Qowim; TM Rais Mujahid Syah (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2023)
Social media has provided many conveniences in the lives of the wider community. And especially in the world of education at this time. However, there are also many problems caused by social media. The research method used is qualitative field research where the researcher conducts research by means of observation, interviews and documentation. This study aims to determine the role of Islamic religious education teachers in overcoming the negative impacts of social media. The results of the research obtained by researchers are that social media has a very bad impact on students starting from the decline in student interest in learning, many like to follow negative trends, the emergence of habits new ones that are not good for students. The role of Islamic Religious Education teachers as facilitators of overcoming the negative impacts of social media at SMAN 8 Mandua has more or less succeeded in reducing the negative impacts that arise from social media. Some of the methods used by PAI teachers are by carrying out learning outside the classroom and conducting interactive discussions in order to create a better harmonious relationship between teachers and students when they are inside or outside of teaching and learning activities. always set a good example to students, reminding him of things he should pay attention to and how he should behave in his daily social life in public, how to get along with the opposite sex and pay attention to other norms according to Islamic teachings. Programs in schools also require teachers, especially PAI teachers, to build relationships and work together with parents so that they can pay more attention and control their children when using cellphones and especially social media so that children don't spend too much time using social media. Keywords: Role, Overcoming negative impacts, and Social Media